"Local" and "national" transformations: Cultural globalization, heterogeneity, and Malaysian literature in English. (March 2016) - Gabriel, Sharmani Patricia
Much of early critical attention on cultural globalization has centred around the emphasis on homogenization. In recent decades, however, postcolonial scholars have tended to focus on the idea of heterogenization, suggesting that this has perhaps been the major outcome of cultural globalization. For them, globalization has opened a space for the periphery to have a voice, with the authority of the centre subject to question from the margins. Offering an examination of Malaysian literature in English and drawing its main theoretical insights from postcolonial studies, this article argues that the Malaysian nation-state's embrace of globalization, and of English as a prime agent in the globalizing process, has given rise to a context where it is creative writing in the former colonial language that has become the very medium that offers resistance to forms of cultural hegemony embedded in state-sanctioned conceptions of national identity.